Reconciling Techno-simplicity and Eco-complexity for future food security - Poggio, Santiago Luis (2015)
Ecological intensification has been proposed as a paradigm for ensuring global food security while preserving biodiversity and ecosystem integrity. Ecologicalintensification was originally coined to promote precise site-specific farming practices aimed at reducing yield gaps, while avoiding negative environmental impacts (techno-simplicity). Recently, it has been extended to stress the importance of landscape complexity to preserve biodiversity and ecosystem services (eco-complexity). While these perspectives on ecological intensification may seem distinct, they are not incompatible and should be interwoven to create more comprehensive and practical solutions. Here, we argue that designing cropping systems to be more diverse, across space and time would be an effective route to accomplish environmentally-friendly intensification of crop production. Such a novel approach will require better integration of knowledge at the landscape level for increasing agro-biodiversity(focused on interventions outside fields) with strategies diversifying croppingsystems to manage weeds and pests (focused on interventions inside fields).